The Effectiveness of Problem-Based Learning Assisted by Animated Videos in Improving Critical Thinking Skills - Nurul Khoiriyatul, Firda; Aziz, Abdul (Universitas Negeri Semarang, 2025)
This study aims to analyze the effectiveness of problem-based learning (PBL) assisted by animated video in improving students' critical thinking skills in class XI SMA Negeri 1 Sragen. This type of research is quasi-experimental in the form of a nonequivalent control group design. The sampling technique used is purposive sampling. Then this study has 2 classes, XI Economics-3B as an experimental class and XI Economics-E as a control class. This study used a paired sample t-test to test the hypothesis and an N-gain score to examine the effectiveness of the teaching and learning model. The result of data analysis in the experimental class has Sig. value (2-tailed) of 0,001, which is less than the level of significance, 0.05. This indicates that there are significant differences between the classes that used animated video as a teaching medium and those that followed conventional teaching methods. The result of the effectiveness analysis N-gain test obtained a score of 0.42, meaning that the effectiveness of the learning model applied in the experimental class is included in the medium category. This study concludes that there are differences in the problem-based learning (PBL) model assisted by animated video in strengthening the critical thinking skills of students in class XI at SMA Negeri 1 Sragen.